Working through the past : labor and authoritarian legacies in comparative perspective - Caraway, Teri L.; Cook, Maria Lorena; Crowley, Stephen, 1960-; Caraway, Teri L. (EBL-Schweitzer, 2015)
"Democratization in the developing and postcommunist world has yielded limited gains for labor. Explanations for this phenomenon have focused on the effect of economic crisis and globalization on the capacities of unions to become influential political actors and to secure policies that benefit their members. In contrast, the contributors to Working through the Past highlight the critical role that authoritarian legacies play in shaping labor politics in new democracies, providing the first cross-regional analysis of the impact of authoritarianism on labor, focusing on East and Southeast Asia, Eastern Europe, and Latin America. Legacies from the predemocratic era shape labor's present in ways that both limit and enhance organized labor's power in new democracies. Assessing the comparative impact on a variety of outcomes relevant to labor in widely divergent settings, this volume argues that political legacies provide new insights into why labor movements in some countries have confronted the challenges of neoliberal globalization better than others."--Publisher's website